Research on Property of Multicomponent Thickening Water Fracturing Fluid and Application in Low Permeability Oil Reservoirs - Chengli Zhang; Peng Wang; Guoliang Song (Journal of Chemistry)
The clean fracturing fluid, thickening water, is a new technology product, which promotes the advantages of clean fracturing fluid to the greatest extent and makes up for the deficiency of clean fracturing fluid. And it is a supplement to the low permeability reservoir in fracturing research. In this paper, the study on property evaluation for the new multicomponent and recoverable thickening fracturing fluid system (2.2% octadecyl methyl dihydroxyethyl ammonium bromide (OHDAB) +1.4% dodecyl sulfonate sodium +1.8% potassium chloride and 1.6% organic acids) and guar gum fracturing fluid system (hydroxypropyl guar gum (HGG)) was done in these experiments. The proppant concentration (sand/liquid ratio) at static suspended sand is up to 30% when the apparent viscosity of thickening water is 60 mPa·s, which is equivalent to the sand-carrying capacity of guar gum at 120 mPa·s. When the dynamic sand ratio is 40%, the fracturing fluid is not layered, and the gel breaking property is excellent. Continuous shear at room temperature for 60 min showed almost no change in viscosity. The thickening fracturing fluid system has good temperature resistance performance in medium and low temperature formations. The fracture conductivity of thickening water is between 50.6 μm2·cm and 150.4 μm2·cm, and the fracture conductivity damage rate of thickening water is between 8.9% and 17.9%. The fracture conductivity conservation rate of thickening water is more than 80% closing up of fractures, which are superior to the guar gum fracturing fluid system. The new wells have been fractured by thickening water in A block of YC low permeability oil field. It shows that the new type thickening water fracturing system is suitable for A block and can be used in actual production. The actual production of A block shows that the damage of thickening fracturing fluid is low, and the long retention in reservoir will not cause great damage to reservoir.